2016
DOI: 10.1002/joc.4634
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional structure and long-term trend of heat wave events in western Eurasia revealed with an anomaly-based approach

Abstract: In the summer of 2010, western Russia experienced extreme heat, which was noted for its exceptional spatial spread, long duration, high intensity and impacts. We use an anomaly-based approach to decompose atmospheric variables into daily climatic components and anomalies from two reanalysis datasets. We show that a surface heat wave event results from a downward extension of an anomalously warm air column below a centre of positive geopotential height anomalies in the upper troposphere. Therefore, we use this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 41 publications
2
11
0
Order By: Relevance
“…Most of the disturbances appear 1–2 weeks before the onset of the heat waves in China. These disturbances are different from those quasi‐stationary systems of height and temperature anomalies responsible for heat wave events in western Eurasia during 1980–2014 (Qian et al , ). Qian et al () suggested that the rapid increase in regional heat wave events over western Eurasia since 2010 is a direct response to the increasing frequency of large‐scale, quasi‐stationary positive centres of maximum height anomalies in the upper troposphere.…”
Section: Conclusion and Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Most of the disturbances appear 1–2 weeks before the onset of the heat waves in China. These disturbances are different from those quasi‐stationary systems of height and temperature anomalies responsible for heat wave events in western Eurasia during 1980–2014 (Qian et al , ). Qian et al () suggested that the rapid increase in regional heat wave events over western Eurasia since 2010 is a direct response to the increasing frequency of large‐scale, quasi‐stationary positive centres of maximum height anomalies in the upper troposphere.…”
Section: Conclusion and Discussionmentioning
confidence: 77%
“…These disturbances are different from those quasi‐stationary systems of height and temperature anomalies responsible for heat wave events in western Eurasia during 1980–2014 (Qian et al , ). Qian et al () suggested that the rapid increase in regional heat wave events over western Eurasia since 2010 is a direct response to the increasing frequency of large‐scale, quasi‐stationary positive centres of maximum height anomalies in the upper troposphere. The frequency change could be due to recent Arctic temperature amplification (Cohen et al , ) and enhanced persistence of the summer season atmospheric circulation over Europe (Kyselý, ).…”
Section: Conclusion and Discussionmentioning
confidence: 77%
“…The common feature observed in all global heat wave cases is the presence of a high-pressure synoptic system (anticyclone) (Black et al, 2004;Dole et al, 2011;Barriopedro et al, 2011;Parker et al, 2014;Murari et al, 2015;Wang et al, 2017). In addition, the heat waves are in general associated with pressure, temperature, geopotential height, and wind anomalies (Deshpande and Ernestraj, 2007;Cerne et al, 2007;Murari et al, 2015;Lee and Lee, 2016;Qian et al, 2016;Rohini et al, 2016;Chen et al, 2017). Also, the occurrence and longevity of heat wave can be governed by specific synoptic conditions.…”
Section: The Role Of Atmospheric Circulationmentioning
confidence: 99%
“…Both GHGs and stratospheric ozone depletion have contributed to the observed poleward shift of the southern Hadley Cell border and the positive trend in the Southern Annular Mode in Austral summer [8]. The changes in the broad-scale circulation patterns have an important impact on regional temperature conditions [9][10][11]. A number of studies have shown that the rate of warming varies by region, climate and study period, and different measures of temperature extremes may present different trends [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…In India, the frequency of cold nights decreased considerably over 1969-2005 and the trends in the number of warm days increased significantly only in the interior peninsula [7,14,15]. In western Eurasia, a rapid increase in regional heat waves was observed since 2010, which was associated with the increasing frequency of large-scale, quasi-stationary positive centers of maximum height anomalies in the upper troposphere and the phase change of the Atlantic Multi-decadal Oscillation (AMO) [9,16,17]. The regional differences in historical trends of extreme temperatures need to take into account projected temperature increases under climate change scenarios and assessment of the impacts of climate change.…”
Section: Introductionmentioning
confidence: 99%